Subacute Histoplasmosis with Focal Involvement of the Epiglottis: Importance of Differential Diagnosis - F. Ahumada; D. Pérez; M. de Górgolas; B. Álvarez; A. Ríos; A. Sánchez; JM. Villacampa (Case Reports in Otolaryngology)
Histoplasmosis is an endemic mycosis of the Americas, Africa, and Asia. In Spain, it is the most common imported endemic mycosis appearing in the literature, and its incidence is on the rise. Proper differential diagnosis of the disease must be taken into consideration by otorhinolaryngologists, as the clinical manifestations of histoplasmosis may simulate more prevalent diseases such as cancer or tuberculosis. We present the case of a Spanish patient with focal involvement of the larynx and offer a review of the relevant literature.